A guide to a somatic movement practice : the anatomy of center - Topf, Nancy; King, Hetty (University Press of Florida, 2022)
"In this introduction to the work of somatic dance education pioneer Nancy Topf, readers are ushered on a journey to explore the movement of the body through a close awareness of anatomical form and function"--